Studies on Human Thyroxine-Binding Globulin: VI. THE NATURE OF SLOW THYROXINE-BINDING GLOBULIN - Marshall, James S. (1972)
A model system utilizing a highly purified partially desialylated thyroxine-(T(4)) binding protein (STBG) was studied. STBG was prepared by the same affinity chromatographic method we have reported for preparation of highly purified T(4)-binding globulin (TBG). The necessary prerequisite for preparation of STBG was the use of T(4)-substituted Sepharose which had been repeatedly exposed to large volumes of serum for purification of TBG. STBG moved more slowly on cellulose acetate electrophoresis than TBG but had the same molecular weight and antigenic determinants as TBG. It bound T(4) with a 1: 1 molar ratio but its affinity for T(4) was about 10 times less than that of TB. STBG had about onefourth the sialic acid content of TBG and the electrophoretic mobility of this protein was similar to that of a T(4)-binding protein with a mobility slower than that of TBG which has been seen in the electrophoretic patterns of some normal human serums and in serums of patients with hepatic cirrhosis and which does not appear to be an artifact caused by storage and freezing of serum. This fourth slowly migrating T(4)-binding region in electrophoretograms of cirrhotic serums is completely abolished by prior incubation with rabbit antiserum to TBG. The in vitro production of partially desialylated TBG from T(4)-Sepharose which had been previously exposed to large volumes of serum may be due to adsorption of neuraminidases to the Sepharose either directly from serum or as the result of bacterial contamination. Partial desialylation of TBG in vivo may be an early step in the catabolism of this protein.